Importance of Cardiac Murmur in Diagnosing Congenital Heart Disease in Neonatal Period - Hoque, Md Mahbubul; Begum, Jotsna Ara; Jahan, Rawshan; Chowdhury, MAK Azad; Hussain, Manzoor (Bangladesh Journal of Child Health, 2010)
Introduction: Congenital heart diseases (CHD) are serious problem of perinatology, occur in 8/1000 live birth. Approximately one third of these neonates require intervention in the first month of life. Clinical features of CHD vary according to type of lesion. Presence or absence of a murmur does not assure either the presence or absence of significant CHD. This study was conducted to determine the clinical and echocardiographic evaluation of neonate with heart murmur and contribution of neonatal examination especially presence or absence of cardiac murmur in the detection of CHD. Method: The study was carried out in Special Care Baby Unit of Dhaka Shishu Hospital during the period from January 2004 to December 2004. Neonates having heart murmur or when there were some clues to doubt CHD like cyanosis, respiratory distress, heart failure, persistent low partial pressure of oxygen(PaO2) in arterial blood gas analysis were underwent echocardiography. CHD were classified according to the structural defect with the echocardiographic findings. Results: Total 812 neonates were admitted during one year period. Heart murmurs were found in 33 cases. Out of 33 cases 15 (45.45%) had CHD confirmed by echocardiography. Another 7 neonates were found to have CHD without murmur after echocardiography. In total 22 (2.7%) neonates had CHD. Pattern of CHD were Ventricular Septal Defect (VSD), Atrial Septal Defect (ASD), Transposition of Great Arteries (TGA), Tetralogy of Fallot (TOF) and Complex cyanotic heart disease. Conclusion: Infant with CHD may present with or without murmur. Careful clinical examination is mandatory in the initial evaluation of neonates to identify CHD. The infant having suggestive features for CHD with or without murmur should undergone echocardiography, so that appropriate intervention and counseling can be done. Key words: neonates; murmur; CHD. DOI: 10.3329/bjch.v32i1.6008 Bangladesh Journal of Child Health 2008; Vol.32(1): 17-20